2011
DOI: 10.1038/ejcn.2011.69
|View full text |Cite
|
Sign up to set email alerts
|

Does the Mediterranean dietary pattern or the Healthy Diet Index influence the risk of breast cancer in a large British cohort of women?

Abstract: Background/Objective: To assess the risk of developing breast cancer associated with consumption of two common dietary patterns: a Mediterranean dietary pattern and a dietary pattern, which conforms to the World Health Organization Healthy Diet Index (WHO HDI). Subjects/Methods: Dietary data from a 217-item food frequency questionnaire were used to generate two dietary patterns according to pre-defined criteria in women from the UK Women's Cohort Study. Survival analysis using Cox regression was used to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
60
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 48 publications
(52 reference statements)
6
60
1
3
Order By: Relevance
“…7 Epidemiological research into the effect of an a priori MD pattern on BC remains limited. To our knowledge, three cohort studies (based on the United Kingdom, 8 Greece 9 and the United States 10 ) and two population-based case-control What's new? Many factors can affect susceptibility to breast cancer, including menopausal status and diet.…”
mentioning
confidence: 99%
“…7 Epidemiological research into the effect of an a priori MD pattern on BC remains limited. To our knowledge, three cohort studies (based on the United Kingdom, 8 Greece 9 and the United States 10 ) and two population-based case-control What's new? Many factors can affect susceptibility to breast cancer, including menopausal status and diet.…”
mentioning
confidence: 99%
“…This study found that the "Vegetable, Fruit, Milk, Poultry, and Fish" pattern, derived via PCA, was inversely associated with breast cancer (OR Q4vsQ4 =0.26; 95 % CI 0.17-0.42; p trend ≤0.001). Two studies [13,21] found no association and two studies [12,23] found a positive association between healthy dietary patterns and breast cancer risk. Buck and colleagues [21] conducted a large population-based case-control study in postmenopausal German women to examine PCAderived dietary patterns and breast cancer risk.…”
Section: Healthy/fruit and Vegetablementioning
confidence: 99%
“…Weak associations were observed between some of the individual components of both of the Mediterranean diet scoring methods and cancer risk; however, when combining the components into a dietary pattern, those with the highest adherence to the Mediterranean dietary pattern had significantly lower odds of developing cancer compared with those in the lowest quartile of adherence (odds ratio (OR) Q4vs.Q1 0.67; 95 % confidence interval (CI) 0.49-0.92; p trend ≤0.0001). Cade et al [13] also examined adherence to the Mediterranean Diet Score (MDS) and the World Health Organization Healthy Diet Index (WHO-HDI) and breast cancer risk in a cohort of 33,731 premenopausal and postmenopausal women from the United Kingdom Women's Cohort Study. The MDS was defined by Trichopolou and colleagues [15] and placed emphasis on legumes, fruits, vegetables, and fish among other foods.…”
Section: Mediterranean Dietmentioning
confidence: 99%
See 2 more Smart Citations